THE EFFECT OF MARKETING COMMUNICATION MIX ON CUSTOMERS’ PURCHASING DECISION: Study on the Customers of Ramayana Department Store, Malang - Ayuni Berta Anugrahsari; Fatchur Rohman (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study aims to examine the effect of Marketing Communication Mix on Customers Purchasing Decision at Ramayana Department Store Malang. The regression analysis, F test and t test were conducted in order to acknowledge the relationships among the independent variables (Advertising, Sales Promotion, Direct Marketing, Personal Selling and Public Relation) on Customer’s Purchasing Decision This study is explanatory research, in accordance with its purpose to determine the causal relationship among variables through hypothesis testing. The samples in this research were the customers of Ramayana Department Store Malang. The data collection method of this study by distributed questionnaire. The sampling technique used is Purposive sampling and the research instruments were tested using the validity test, reliability test, and classical assumption test. The hypothesis testing used the F test and t test in Multiple Regression Analysis. The multiple regression analysis showed that simultaneously, Advertising, Sales Promotion, Direct Marketing, Personal Selling, and Public Relation had significant effect on Customer’s Purchasing Decision. Meanwhile, partial test shows that the variables of Advertising, Sales promotion and Personal Selling had significant effect on Customer Purchasing Decision. However, the variables of Direct Marketing and Public Relation had no significant effect on Customer’s Purchasing Decision. The dominant test shows that Personal Selling has dominant effect on customer’s purchasing decision.Keywords: Marketing Communication Mix, advertising, sales promotion, direct marketing, personal selling, public relation, customer’s purchasing decision.